CD8+ T cells are increased in the subventricular zone with physiological and pathological aging. Issue 9 (1st August 2020) - Moreno‐Valladares, Manuel; Moreno‐Cugnon, Leire; Silva, Tulio Mateo; Garcés, Juan Pablo; Saenz‐Antoñanzas, Ander; Álvarez‐Satta, María; Matheu, Ander
Abstract: Age‐related cognitive decline and neurodegenerative diseases are associated with less functional neurogenic niches. It has been recently shown that aged subventricular zone (SVZ) suffers an infiltration of T cells, which affects neural stem cell activity in mice. Whether this occurs in human neurogenic niches or to which extent T‐cell infiltration is also taking place in neurodegenerative diseases remains unknown. In this work, we studied the presence of T cells in both human neurogenic niches in young and old individuals. There was a significant increase in the number of CD3 + and CD8 + T cells in the SVZ of elderly individuals, which was not detected in the dentate gyrus. Moreover, we also found CD3 + and CD8 + T cells in the SVZ of individuals with neurodegenerative diseases. However, T‐cell count was similar when compared non‐neuropathological elderly with disease diagnosed patients. Our study reveals the infiltration of T cells in old human brains, particularly in the SVZ under non‐pathological conditions and also in neurodegenerative contexts. Abstract : Representative image of CD8 in subventricular zone of young and old individual